(untitled) (Journal of Dhaka Medical College, 2020)
Background: Candida species are responsible for various clinical infections ranging from mucocutaneous infection to life threatening invasive diseases. Recently there is a serious concern with increased resistance of antifungal drugs and its consequences. Thus, identification of Candida and its antifungal susceptibility testing has a paramount significance in the management of Candidal infections. The aim of the study was to determine antifungal susceptibility pattern of Candida by Mueller-Hinton agar media supplemented with glucose and methylene blue for disk diffusion testing of fluconazole, miconazole, clotrimazole, amphotericin B and nystatin. Methods: A total of 35 Candida species was isolated from 2000 clinical specimens over 6 month’s period from July 2016 to December 2016. Growths on Blood agar and chromogenic agar were evaluated for colony appearance and microscopic examination. Antifungal susceptibility testing was performed by disk diffusion using Mueller-Hinton agar supplemented with glucose and methylene blue. Results: Candida species were more sensitive to clotrimazole (88.58%) and amphotericin B (88.58%) followed by nystatin ((77.14%), miconazole (74.29%) whereas fluconazole showed the highest level of resistance (60%). Conclusions: The increase in resistance to fluconazole is of serious concern as it is the most commonly used azole for candidiasis. The sensitivity profile of Candida isolates will be helpful to choose appropriate antifungal agents, thus decreasing patient’s morbidity and mortality. J Dhaka Medical College, Vol. 28, No.1, April, 2019, Page 28-33